Factors related to living alone in people over 60 years in Bogotá, Colombia - Chavarro-Carvajal, Diego A. (2021)
Objective: to identify the factors related to living alone and the magnitude of its effect on the adult population over 60 years old living in community in the city of Bogotá. Methods: cross-sectional study with secondary analysis of the Health, Well-being, and Aging Survey (SABE) - Bogota 2012. Measurements of central tendency were calculated, the means were compared with Student's t-test, the final model was adjusted for age, gender, and the odds ratios (OR) and their CI 95% were calculated to estimate the power of the relation. Results: out of the 2,000 people who participated in the SABE survey, 252 (12.6%) lived alone. The average age was 71.32 years; 64.68% were women (n = 163). The average schooling was 6.19 years (SD 0.31). When making the bivariate analysis, a statistically significant relation was found between living alone and being independent for basic and instrumental activities of daily living, absence of dementia, and good self-perception of health condition. In the logistic regression model, not having a partner (OR 4.91 CI 95% [3.61-6.68]), absence of dementia (OR 2.77 CI 95% [1.94-6.16], poor self-perception of nutritional condition (OR 1.7 CI 95% [1.24-2.33] and female gender (OR 1.37 CI 95% [1.03-1.91] were significantly associated with the possibility of living alone in people over 60 years. Conclusions: this study found that in people living alone there is not only an association with not having a partner, but also with having a good cognitive state, being a woman, and a poor self-perception of the nutritional condition.